(untitled) (Research, Society and Development, 2021)
Allelopathy is an ecological mechanism that influences the development of neighboring plants. The objective was to evaluate the allelopathic potential of Cenostigma bracteosum and Sarcomphalus joazeiro on seed germination and initial growth of Mimosa caesalpiniifolia seedlings. Seeds of this species were placed to germinate on paper towel substrate, and then moistened with extracts from dry leaf of S. joazeiro and C. bracteosum at 1.0; 2.5; 5.0 and 10.0% (w.v-1), and control (0.0% - distilled water) at 25 °C. The variables evaluated: germination, germination speed index, primary root length and root system dry weight of the seedlings. Positive allelopathic effects of S. joazeiro leaf extracts were observed on the vigor of M. caesalpiniifolia; when used in low concentrations (up to 2.6%), C. bracteosum leaf extracts stimulated germination of M. caesalpiniifolia seeds and showed more severe toxic effects when exposed to high concentrations (5.0%). S. joazeiro leaf extracts favor the germination and vigor of M. caesalpiniifolia seedlings, while C. bracteosum leaf extracts cause phytotoxic effects on seed germination and initial growth of M. caesalpiniifolia seedlings from the concentration of 5%. Therefore, there are indications of benefits for regeneration or associated forest composition between M. caesalpiniifolia and S. joazeiro.